Misconduct and leader behaviour in contests: New evidence from European football - Karol Kempa; Hannes Rusch (Philipps-University Marburg, School of Business and Economics, 2016)
This paper provides an empirical investigation of severe misconducts in contests based on data from European football championships. We differentiate between two types of severe misconducts both resulting in a yellow card, namely dissents with the referee and other misconducts, and between sanctioned behaviour of team captains and other players. Confirming the existing literature, we find that sabotage against the opponent is used more frequently by players from teams with lower ability. In addition, we find that dissents with the referee are significantly more likely in the case of an unfavourable score. We further find that captains, in contrast to other players, seem to use sabotage less impulsively and more strategically, as they do not seem to participate in retaliatory escalation of conflict behaviour. However, compared to other players, captains increase their sabotage in important matches.
Keywords: D74; L83; M52; 330; Contest; Dissent; Leadership; Sabotage; Football